The Effect of Parental Emotional Stability among Indian Adolescent’s Psychosocial adjustment in Kerala, India - Joseph, Sindhu; Varma, Parvathy (Scholar: Human Sciences, 2017)
In India, the emotional stability of the parents has become an increasingly serious societal issue but unfortunately, it is not given importance within the Indian context. To help address this problem, the present study attempted to investigate the influence of perceived parental emotional stability on adolescents’ psychosocial adjustment being mediated by parental bond, family relationship, and parental self-efficacy. The results of the study found that the higher the participants’ perception of their parental emotional stability, the more positive the perception of their family relationship, the higher the perception of their parental self-efficacy and subsequently, the higher is their reported level of psychosocial adjustment. It also found that the higher the participants’ perception of their parental emotional stability, the lower the perception of their parental bonding, the higher the perception of their parental self-efficacy and subsequently, the higher is their reported level of psychosocial adjustment.